Japanese Language Learners of Manado State University's Ability to Produce Long Duration Vowels /AA/, II/, /UU/, /EE/ and /OO/ - Pandi, Helena Maria Lidwina; Lensun, Sherly F; Sompotan, Amelia; Aror, Susanti (Vocational College of Diponegoro University, 2024)
Mastery of long vowel pronunciation in Japanese is an important aspect for learners, especially at Universitas Negeri Manado. Long vowels, such as /AA/, /II/, /UU/, /EE/, and /OO/, have a longer duration than short vowels. The purpose of this study was to determine the duration of long vowels produced by students of the Japanese Language Education Study Program and how they differ when compared to native speakers. This research was conducted on students of semester IX (nine) of Japanese Language Education Study Program of Universitas Negeri Manado and a native speaker. The method used is descriptive quantitative where the author processes the data recorded by the speakers using Speech Analyzer application which is a software application to analyze speech sounds to obtain data on the duration of long vowels. After that, it was processed again using Microsoft Excel to calculate the average duration of long vowels from the speakers' speech. The conclusion of this study is the duration of long vowels produced by students from the average obtained are: 149 ms on the vowel /aa/, 142 ms on the vowel /ii/, 127 ms on the vowel /uu/, 251 ms on the vowel /ee/, and 122 ms on the vowel /oo/. The duration mentioned above after being compared with native speakers the results tend to be shorter than native speakers. There are also significant differences with native speakers in some vowel positions in words such as the sound /_aa/ by AK (093 ms), JE (084 ms) and native speakers (195 ms).